Two isolated crystalline solids from the stem of Entada spiralis Ridl.(akar Sintok) = Pemencilan dua jenis pepejal kristal dari batang pokok Entada spiralis (Akar Sintok) - Harun, Aiza; Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian (The Malaysian Analytical Sciences Society, 2016)
Entada spiralis Ridl. (Leguminosae) is a woody climber which locally known as ‘akar sintok’. The isolation and structure determination of two crystalline solids from active methanol fraction of E. spiralis stem bark had been examined. The structure identification of both solids was based on spectroscopic data (1 H and 13C NMR, HMQC, HMBC, DEPT135 and MS) along with comparison with literature data. The results revealed that these two crystalline solid sugars isolated from the most active fraction were known as penta-2-acetoxy-β-D-digitoxopyranosyl-(1→2)-fructofuranosyl-(6→4)-β-D-glucopyranosyl-(1→4)- glucopyranosyl-(1→2)-β-D fructofuranosyl-(6→1)-β-D-glucopyranosyl-(4→1)-acetylglucosamine (1) and β,D-glucopyranosyl(1→2)-β,D-glucopyranosyl)-(1→3)-β,D-xylopyranosyl(1→4)-α,L-rhamnopyranosyl)-(1→3)-β,D- glucopyranosyl(1→3)- β,D-glucopyranoside (2) Thus, this finding can be utilized as a scientific baseline information for further skin disease studies, since both constituents were isolated from moderate antidermatophytic active fraction.